One‐pot peptide cleavage and macrocyclization through direct amidation using triazabicyclodecene. Issue 4 (24th March 2020) - Hickey, Jennifer L.; Lin, Songnian
Abstract: We have developed a novel protocol for a one‐pot cleavage from solid support and subsequent cyclization to form small macrocyclic peptides. Synthesized on a 4‐hydroxymethyl benzamide (HMBA) resin, the peptides are cleaved from the solid support through a 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) assisted acyl transfer reaction. The resulting linear peptides then undergo an intramolecular cyclization, presumably upon in situ attack of the N ‐terminal amine on the TBD‐activated ester. This protocol requires catalytic quantities of TBD and eliminates the need for orthogonal side chain deprotection strategies and ether trituration/work‐up steps, streamlining the synthesis of head‐to‐tail macrocyclic peptides. Abstract :